Criminal Cases of Socially Maladjusted Schoolchildren (Archives of Criminology, 1984)
1. The study discussed in the present paper is a continuation of the research on extent and determinants of social maladjustment among schoolchildren in Warsaw elementary schools, which was conducted in the years 1976-1979. Over 600 classes (grade III-VIII) were then examined, which makes the total numer of 17,662 children aged 9-16. Teachers indicated children who revealed symptoms of social maladjustment (such as regular truancy, many-hours loitering around the streets without control, running away from home, stealing, frequenting company of demoralized colleagues, drinking alcohol, sexual demoralization, vandalism and frequent aggressive behaviour). 885 boys (which makes 10 per cent of all schoolboys included in the study) and 220 girls (2.7 per cent of all girls) were found to reveal these children, which included information as to the child’s family environment, school situation, school failures, behaviour, health, and symptoms of social maladjustment.       From this general popuration of 885 schoolboys who revealed symptoms of social maladjustment, a group of 262 boys was separated  whose symptoms were particularly intense and cumulated. This group then underwent a detailed individual examination.      As a control group to match this group of 262 boys whose symptoms of social maladjustment were cumulated and intense, 151 boys were drawn by lot from among those of all schoolboys who had not been mentioned by the teachers as children who reveal symptoms of social maladjustment, and who were classmates of the socially maladjusted boys. The control group underwent the same individual examination.      2. At the stage of the study presented in the present paper the aim was to answer the following questions:                                                                                                                                                                     - how many of the schoolchildren indicated by the teachers because of various symptoms of social maladjustment had cases in court before they were included in the study.                                                 – how many of them  had cases in court during the five years of follow-up study.                                      – what was the total number of children who had ever had cases in court and what was the intensity of their criminal careers.                                                                                                                                             –is there any difference between the socially maladjusted schoolchildren who had cases in court and those with a clean record, as regards any features of their  family environment or the kind of symptoms of social maladjustment, which caused  them to be included in the study. Is there any difference between them as regards their school failure or the results of psychological examination.      In order to answer these questions, in mid 1982 it was checked if the children indicated as socially maladjusted had cases in court as juveniles or as young adults (aged 17 and over). The examined persons were then aged 15-23. The cases of persons concerning whom it was impossible to obtain data, as to their criminal record were excluded from the analysis therefore, finally the examined population consisted of 859 boys and 220 girls.       3. At the moment when the examined schoolchildren were indicated by the teachers as revealing symptoms of social maladjustment, 6.9 per cent of the socially maladjusted boys and 3.7 pet cent of  the girls had criminal cases in family courts.  A considerable majority of these children (5.1 per cent of the boys and all girls, 3.7 per cent) had only one case in court. The cases occurred generally at the age 14-16. The number of children who had had cases of care and protection during anamnesis is comparatively large: 5.5 per cent of boys and as many as 16.3 per cent of girls.      The examination of the schoolchildren's further criminal careers during the following 5 years produced the following results:                                                                                                                             - 20.9 per cent of boy  were convicted by courts within that period (10.2 per cent had cases in family courts, 5.7 per cent- in ordinary courts, 5 per cent- both in family and in ordinary courts).                        - 4 per cent of girls were convicted (3.6 per cent by family courts, 0.4 per cent by  ordinary courts).          It should be added that on account of the age, only 629 boys and 178 girls could have had cases in ordinary courts. Among them, 14.8 per cent of boys and one girl were convicted. The percentage is high, as part of those who „could have had cases" were only 17 years old, the probability of their conviction being  thus minimal.          25.7 per cent of boys convicted by ordinary court committed aggressive acts, while 70.7 per cent were convicted only for offences against property.      When the entire examined  period (anamnesis and follow-up period) is discussed together, it appears that every fourth boy (23.4 per cent) and every thirteenth girl among all socially maladjusted children were delinquent. This result certifies to the generally known difference between the extents of delinquency of boys and girls. However,  the represented proportion changes diametrically if one takes into account not only criminal cases, but also those of care and protection. 12.2 per cent of boys and as many as 25.4 per cent of girls had cases of care and  protection in family courts. There were  26.4 per cent  of socially maladjusted boys and 28.6 per cent of girls who had cases in family courts (criminal and care and protection together). The high percentage of girls who had  cases of care and protection may be connected to their worse family  situation which demanded intervention, as well as with the fact, that girls revealed  symptoms of sexual demoralization more frequently than boys (as many as 1/5 of socially maladjusted girls in grade VIII); these  symptoms awoke concern of the adult and may induce them to seek intervention of a court. Such symptoms, not being offences, may only be a reason for instituting tutelar proceedings.      Another problem was also examined, that is of the features of the examined persons and of their  family environment (as revealed by the questionnaires  filled in by the  teachers) which would differentiate the delinquent boys from those who had never been convicted. The delinquent boys were found to live in worse family backgrounds, in which criminality of parents or siblings or alcoholism of the father  occurred more frequently.  Instead, the delinquent boys were not found to live more frequently in broken homes or separately from their  parents. The delinquent boys were more socially maladjusted than those never convicted: they revealed a greater numer of symptoms of social maladjustment, their teachers informed more frequently of threir thefts, drinking, contacts with demoralized colleagues, and truancy. Instead, the delinquent boys were not described by the teachers as fighting with their schoolmates „often” and „very often”  more frequently than those never convicted.  It may be that such a description of a child by the teacher was unreliable;  the boy's aggressive behaviour may have been  a temporary phenomenon, resulting from actual  social situation; aggressiveness revealed at school may have been separate from the entire syndrome of social maladjustment. However, at the present stage of the study we are not in a position to take up any attitude towards these possible explanations. Neither the many-hours loitering around the streets was found to significantly differentiate the delinquent boys from those never convicted. This results from the fact that loitering is a typical way of spending time of the considerable majority of socially maladjusted boys, therefore it does not differentiate those who were convicted from the others.        4. In the group of 262 individually examined boys who revealed intense and cumulated symptoms of social maladjustment, the extent of delinquency appeared to be larger than in the entire population of 885 socially maladjusted schoolboys from which this group has been selected. During anamnesis, 32 per cent of boys had criminal cases in family courts; 78.9 per cent of them had only one case, 18.3 per cent had two cases, and 2.8 per cent -three or more cases. During the follow-up period, 28.2 per cent of the examined boys had cases in court, including 14.1 per cent who had cases in family courts only, 7.6 per cent who had cases in ordinary courts only, and 6.5 per cent who had cases both in family and in ordinary courts. Within the whole of the examined period (both anamnesis and follow-up period), nearly half of the examined boys were convicted: 29.4 per cent  had cases in family courts only, 5.3 per cent- in ordinary courts only, and 14.1 per cent-both in family and in ordinary courts. Therefore, every second  boy from the group with intense and cumulated symptoms of social maladjustment had cases in court within the examined period, while every fourth one from the entire population had been convicted.       Poor material and housing conditions of the family, insufficient care of children, broken home and bad conjugal life of the parents were not found to be significantly connected with the delinquency of the examined boys. Instead, a correlation of statistical significance was found between delinquency and excessive drinking of the fathers, their own criminal records and periods of imprisonment, as well as between the sons' delinquency and the lack of elementary education of the parents.       On the other hand, no difference was found between delinquents and non-delinquents as regards the teachers' estimation of their intelligence level and learning difficulties pointed out by their mothers and themselves. None of the biopsychical variables taken into account in the study was found to differentiate both groups: lowered level of intelligence, eyesight defect, hearing defect,  disturbances of speech, dyslexia, probable past lesions of the central nervous system, troubles with concentration, very slow rate of working. Persisting neurotic symptoms. Indeed, these factors were present rather more frequently among the non-delinquent boys, distinctly connected with their learning problems and school failures. On the other hand, delinquents actually repeated classes more frequently than non-delinquents, got bad marks in various subjects, and their learning progress was estimated as worse by the teachers. Delinquent boys more frequently behaved badly at school beginning from the lowest standards, they played truant from various lessons, were disobedient and disturbed the course of the lessons, had lower marks for behaviour and stated that they did not like school.       The socially maladjusted delinquents used to spend time in company of friends older than themselves more often than the non-delinquent boys; they themselves described those friends as badly behaved and drinking alcohol. They were also substantially more often connected with groups of juvenile delinquents according to the teachers' opinion. They revealed a considerably larger intensity of symptoms of social maladjustment. Among these symptoms, only the frequency of aggressive behaviour failed to differentiate the delinquent and non-delinquent boys, which means that as regards the individually examined group,  the result concerning the entire population was confirmed.        Therefore, the delinquency of the examined persons was related to the greater intensity of their social maladjustment, to their negative family environment and their school situation connected not only with objective learning difficulties but also with the child's reluctant attitude towards school and teachers, and with the teachers' disfavourable opinion of his learning progress and behaviour.       It is also worth mentioning that in the control group of 151 schoolboys who were not indicated by the teachers as revealing symptoms of social maladjustment, only one person was found who had been convicted by court during the entire examined period.